Gêneros multimodais e práticas de letramento em livros didáticos de língua portuguesa - Santos, Manuel Álvaro Soares dos (2019)
The emergence of digital technologies, specifically the computer and smartphones, at the end of the twentieth century, changed and streamlined the way we relate to literacy practices (SOARES, 2002). So, if before our discursive productions were based on logocentrism, that is, the focus on the written word, today, our productions have the possibility of integrating to their compositional structure other semiotic modes such as images, colors, sounds, Layout spacings, movements, etc., which implies the construction of new literacy practices, focusing on the heterogeneity of new uses enabled by digital technologies and the multiplicity of goals now possible in this new Scenario. According to Kress (2003) defends, we need to build a semiotic power capable of orchestrating the multimodality constitutive of the new practices of reading and writing, considering that for the social agency we will need both read and produce multimodal texts In the different spheres of social participation. In view of this, Santaella (2003, 2007) postulates that Cyberculture has inaugurated a new way of relating to language, because the processes of mixing languages become increasingly constant. Thus, our Master's research aims to understand the way multimodality is conceived in the proposals for the activity of the textbooks of Portuguese language of high school, having as corpus two collections approved in the pnld of 2018, namely, the New words and protagonist collections. Our research issues, to a certain extent, are the consequences of our general objective, which focuses on multimodality in LDP and seeks to understand: (a) What are the reflections and refractions of the conception of language and multimodality of official documents, PCNEM, PCN+ and OCEM, in LDP; (B) How multimodality is conceived through the evaluative criteria of the PNLD; and (C) how the writing and reading proposals presented in the LDP represent the conception of literacy with social practices. In Our analysis, we can perceive a mismatch between what the official documents parameterize about multimodality, between what PNLD defends and between the way LDP conceive multimodality in its activity proposals. Some proposals for activities, although present in its textual composition several semiotic modes, cannot articulate them in literacy practices. For this research, the methodological perspective adopted is a qualitative documentary basis, considering the nature of our analysis corpus (MOITA-LOPES, 2013; FLICK, 2009).